Multilevel barriers to clinical and nutritional research in Latin America: a socioeconomic comparative analysis - Frias-Toral, Evelyn; Angamarca-Iguago, Jaime; Calvo Higuera, Isabel; Carriel-Mancilla, Jorge; Contreras, Guillermo; Franco-Nuñez, Raquel; Larreategui Arosemena, Rosa; Maza Moscoso, Claudia; Restrepo, Javier; Cagua-Ordoñez, Jaen; Simancas-Racines, Alison; Reytor-González, Claudia; et al. (Frontiers in Nutrition, 2025)
IntroductionClinical and nutritional research in Latin America faces significant challenges that limit scientific development and evidence-based healthcare. Understanding these barriers is essential for developing effective strategies to enhance research capacity in the region. This study aimed to identify multilevel barriers to clinical and nutritional research in Latin America and compare them between countries of different socioeconomic levels.MethodsA cross-sectional study was conducted with 327 healthcare professionals involved in clinical and nutritional research across Latin America. Data collection occurred via an online survey in which participants rated the importance of 16 potential barriers on a 3-point Likert scale. Analysis included descriptive statistics, chi-square tests to compare barriers between upper-middle and lower-middle-income countries, logistic regression to identify predictors of research participation, and k-means cluster analysis to identify researcher profiles.ResultsFunding (84.4%), research materials (71.6%), and time constraints (70.9%) emerged as the most significant barriers across all countries. Three barriers showed statistically significant differences between income levels: participant commitment (73.6% vs. 42.6%, p < 0.001), frequent appointments (56.6% vs. 37.8%, p = 0.02), and language barriers (39.6% vs. 22.9%, p = 0.02), all of which were higher in lower-middle-income countries. Logistic regression identified the importance of research materials (OR = 0.36, p = 0.002) and telemedicine (OR = 1.74, p = 0.044) as significant predictors of research participation. Cluster analysis revealed three distinct researcher profiles based on barrier perception patterns.ConclusionMultilevel barriers to research in Latin America are dominated by universal resource constraints (funding, materials, time), with lower-middle-income countries facing additional challenges in participant engagement and study logistics. The relative homogeneity of most barriers across income groups suggests that regional and institutional factors may be more influential than national income levels. These findings provide a foundation for developing targeted strategies to strengthen research capacity and infrastructure across Latin America.